2011
DOI: 10.1016/j.acvd.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed airflow limitation in patients at cardiovascular risk

Abstract: Patients with CVD are at increased risk of AL and thus should benefit from AL screening as they are frequently asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 26 30 The inverse situation – an increase in the risk of COPD in patients with a history of cardiovascular disease – has been shown in other studies. 14 , 31 , 32 The worsened prognosis for patients with IHD and COPD together has been demonstrated in various studies carried out in patients with IHD who have undergone PCI. 3 5 , 9 , 11 , 12 Other studies have shown a worse prognosis for patients with COPD and acute myocardial infarction, revealing greater risk of heart failure, bleeding, cardiogenic shock, and mortality.…”
Section: Discussionmentioning
confidence: 97%
“… 26 30 The inverse situation – an increase in the risk of COPD in patients with a history of cardiovascular disease – has been shown in other studies. 14 , 31 , 32 The worsened prognosis for patients with IHD and COPD together has been demonstrated in various studies carried out in patients with IHD who have undergone PCI. 3 5 , 9 , 11 , 12 Other studies have shown a worse prognosis for patients with COPD and acute myocardial infarction, revealing greater risk of heart failure, bleeding, cardiogenic shock, and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Not only do the two diseases share major symptoms such as dyspnoea and fatigue, they also have common etiological factors such as smoking and ageing [58]. Consequently, under- and over-diagnosing COPD in HF patients are common [912]. Also from a therapeutic and prognostic perspective, the coincidence of COPD and HF is relevant.…”
Section: Introductionmentioning
confidence: 99%